Gall Bladder Perforation by Typhoid Complication - Bhandari, RS; Singh, KP (Journal of Nepal Health Research Council, 2009)
Surgical complications of typhoid fever are uncommon and usually when it occurs, it commonly involves gut than the gallbladder. We present a case report of 20years old gentleman who presented with ten days duration of fever and one day history of sudden severe generalized pain abdomen. Patient was evaluated and investigated and undergone laparotomy in the line of peritonitis. Operative finding was gallbladder perforation and he underwent cholecystectomy. Other investigations were supportive of typhoid fever. Patient improved and was discharged after seven days. Key words: gallbladder, perforation, typhoid   DOI: 10.3126/jnhrc.v7i1.2295 Journal of Nepal Health Research Council Vol. 7, No. 1, 2009 April 52-53